Local knowledge, modernization, soil use and management: an etnopedological study on the southern plateau of Santa Catarina (Revista de Ciências Agroveterinárias, 2006)
The etnopedology is the field that studies people knowledge about soil resources, taking into account nature, cultural values and local tradition. Considering that rural development is not only a subject of soil management, this research studied the developmental processes on Santa Catarina’s South Plateau, trying to relate local population knowledge to the use and soil management and its effects on the regional development. The conclusions were that etnopedology instrumental is largely useful for this type of research showing the anthropological bases of soil utilization; and that there are many misunderstandings about popular logic in the region population.
Keywords: regional development; etnopedology; soil use and management.